2004
DOI: 10.5194/angeo-22-2047-2004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in electron and ion temperatures due to solar flares as measured by SROSS-C2 satellite

Abstract: Abstract. The observations on the ionospheric electron and ion temperatures (T e and T i ) measured by the RPA payload aboard the SROSS-C2 satellite have been used to study the effect of solar flares on ionospheric heating. The data on solar flare has been obtained from the National Geophysical Data Center (NGDC) Boulder, Colorado (USA). It has been found that the electron and ion temperatures have a consistent enhancement during the solar flares on the dayside Earth's ionosphere. The estimated enhancement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The model has assumed constant electron temperatures during the flare, whereas basic physical principles predict an increase in electron temperature during a flare. Observations of the terrestrial ionosphere have shown that during a solar flare, electron temperatures at 425–625 km can increase by 1.3–1.9 times [ Sharma et al , 2004]. Neglecting to include an increase in electron temperature would mean that the inferred W‐value is too small.…”
Section: Discussionmentioning
confidence: 99%
“…The model has assumed constant electron temperatures during the flare, whereas basic physical principles predict an increase in electron temperature during a flare. Observations of the terrestrial ionosphere have shown that during a solar flare, electron temperatures at 425–625 km can increase by 1.3–1.9 times [ Sharma et al , 2004]. Neglecting to include an increase in electron temperature would mean that the inferred W‐value is too small.…”
Section: Discussionmentioning
confidence: 99%
“…(10), m avg = 4.8 × 10 −26 kg (Mitra 1992) and ρ = 34 eV (Whitten et al 1965). Using SROSS-C2 satellite data, Sharma et al (2004) measured electron and ion temperature changes of ionosphere and they showed that electron temperature (T e ) changes from 1.3 to 1.9 times and ion temperature (T i ) changes from 1.2 to 1.4 times respectively during flares in comparison with normal days. Thus the change of α ef f due to these T e , T i changes is less enough compared to other ion-chemical effect induced changes.…”
Section: Theoretical Understandingmentioning
confidence: 99%
“…In addition to these general responses to the change of solar activity in the 11 year cycle, the responses in a shorter timescale have also been studied. For example, solar flares were seen to affect total electron content, as well as electron and ion temperatures for the dayside, while the nightside ionosphere was not disturbed much [ Afraimovich et al , 2001; Sharma et al , 2004]. Measurements from the Dynamics Explorer‐2 and Atmosphere Explorer‐C satellites at altitudes of 300 to 400 km indicated that the daytime T e at low latitudes exhibited 27‐day variations [ Brace et al , 1987].…”
Section: Introductionmentioning
confidence: 99%